Effects of long-term physical training on depression in adolescents - Guifang Liu; Yonglei Liu; Haoyuan Li (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
From the standpoint of sports commitment, investigate the influencing variables of personal aspects on teenagers' physical and mental health. Methods: It was discovered that there were gender and grade disparities in teenage stress tolerance after a study of 1000 senior high school students. Teenagers' levels of physical activity, frequency of physical activity, and time spent exercising are all pretty consistent and appropriate. Teenagers' stress resistance, mental health, and interpersonal relationships are all influenced by physical activity. The quantity of physical activity and teenagers' stress tolerance were shown to be positively correlated (P 0.05). It had a favourable relationship with mental wellbeing (P 0.05). There was no statistically significant link between interpersonal relationships (P > 0.05). When the pressures of a teenager's life and studies mount, an appropriate amount of physical activity can effectively adjust their mental health and stress tolerance to a degree, allowing them to continuously vent their negative emotions and relieve the pressure, thus improving their mental health, allowing them to face life positively, and improving their ability to withstand pressure. Conclusion: Sports commitment may completely mobilise social support, promote adolescent happiness through numerous channels, establish a pleasant learning and training life environment, and strengthen positive psychology guidance and development.